Literacy Culture of Islamic Education Teachers in Senior High School of Bengkulu City - Khoiri, Qolbi; Bustomi, Bustomi (Dinamika Ilmu: Jurnal Pendidikan, 2020)
The present article is aimed at revealing and analyzing the literacy culture implemented by Islamic education (PAI) teachers in Bengkulu city. This study explores and analyzes the problem qualitatively. The method used in collecting data is deep observation of 37 SMA(s) in Bengkulu city. In addition, interviews and surveys were also used by distributing questionnaires to representatives of PAI teachers from 37 SMA/SMK when they were invited to attend a workshop on enhancing literacy culture for PAI teachers. After collecting the data, it was analyzed with the Miles and Huberman style flow model, namely data collection, data reduction: the presentation of data in the form of a percentage of indicators of low reading and percentage of written papers made by PAI teachers; and conclusions. The results showed that literacy culture of PAI teachers, in the context of the habit of reading scientific books and writing scientific papers, was a relatively low. This is influenced by the lack of practice and habit of writing scientific papers such as PTK. The use of digital media such as e-book applications, e-learning, and google shcolar for learning is also low. However, teachers always tell students to visit the library to read books when assignments are given. It was followed that the literacy culture of PAI teachers in Bengkulu city is quite good, but the utilization of digital literacy is still low.